The impact of sea bottom effects on the retrieval of water constituent concentrations from multispectral satellite images in complex shallow tidal waters supported by radiative transfer modeling - Arabi, Behnaz; Salama, Mhd. Suhyb; van der Wal, Daphne; Pitarch, Jaime; Verhoef, Wouter (Remote Sensing of Environment, 2020)
Many coastal waters include large areas of Optically Shallow Waters (OSWs) ‎where the sea-bottom affects above-water observations of remote sensing ‎reflectance (Rrs [sr−1]). If not treated, the effect of bottom reflectance will ‎interfere with the correct retrieval of Water Constituent Concentrations ‎‎(WCCs) from hyperspectral and multispectral remote sensing observations. ‎To study this phenomenon in more detail, the existing semi-infinite ‎‎2SeaColour Radiative Transfer (RT) model was modified into a finite water ‎layer model, bounded by a diffusely reflecting surface at the sea-bottom. ‎From simulations with the new model, called Water - Sea Bottom (WSB) ‎model, it was observed that a ratio of spectral bands in the Near-Infrared, ‎bands 750 nm and 900 nm, is nearly insensitive to the WCCs and increases ‎with the shallowness of the water, and therefore can be used as a robust index ‎to detect OSWs. The newly established Near-Infrared Bottom Effect Index ‎‎(NIBEI) was applied to a series of satellite observations over the Wadden Sea ‎during high and low tidal phases. Images from the MEdium Resolution ‎Imaging Spectrometer (MERIS) and the Ocean and Land Colour Instrument ‎‎(OLCI) were processed to retrieve WCCs of the study area. The results indicate ‎that the sea-bottom effect in OSWs affects the accuracy of atmospheric ‎correction and retrievals. On the other hand, applying the NIBEI to flag OSWs ‎improves the reliability and consistency of WCCs maps. The application of ‎proposed NIBEI on satellite images requires only Top Of Atmosphere (TOA) ‎radiances at 750 nm and 900 nm and does not depend on atmospheric ‎correction and ancillary local input data (e.g., bathymetry map, bottom type, ‎empirical coefficients, in-situ measurements). As a result, the proposed NIBEI ‎can readily be applied to detect OSWs on various ocean colour remote sensors ‎in various shallow coastal regions.‎‎
Keywords: Remote sensing; Water quality monitoring; OLCI; Sentinel-3; MERIS; Optically shallow waters; Tidal waters; The Wadden Sea; Sea-bottom effect; Radiative transfer modeling; MODTRAN; 2SeaColour